Analytical Hierarchy Process Approach on Regional Product Competitiveness in Magelang, Central Java - Nuryadin, Didi; Sodik, Jamzani (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2017)
This study aims to identify and analyze the data and information to determine the local featured products through the aspects of value-added, market expansion and production technology. The location is the town of Magelang in which there are many small and medium industries with a wide range of their products. The analytical tools used include common analytical technique used to determine a featured product. They are scoring, value chain and Analytical Hierarchy Process (AHP). The result of the study shows that the main criteria for weighting the featured products are competitive advantage, stakeholders' acceptance and societal benefits. Through all three criteria, there are three main local featured products becoming the. They are getuk (the result of processed cassava), kerupuk tahu (tofu crackers) and ceriping ketela (cassava crackers). Furthermore, through a comparative analysis of the criteria, it can be concluded that the product getuk can be considered as the Regional Industry Core Competence based featured product from Magelang.Keywords: Analytical Hierarchy Proces, Regional Product, Competitiveness